Introduction of the unified communications information system E-112 - Petreski, Drage T.; Iliev, Andrej P.; Petreska, Aleksandra D. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The introduction of the European emergency number 112 in the Republic of Macedonia should provide benefits that will be implemented and regulated in accordance with the European legislative framework. This number has already provided numerous benefits to all member states of the European Union. Its implementation should be supported by the introduction of the latest technology information and communication solutions, hardware and software solutions tailored to the situation in the country. It will replace four current phone numbers for emergency calls that are a responsibility of the Ministry of Interior (192), local fire units (193), emergency care (194) and the Center for Crisis Management (195). These numbers are planned to be replaced by the European emergency number 112 together with its full implementation into the integrated information - communication center.
Keywords: European number 112; solutions; information systems; Implementation; countries; Communities; benefit; unification